2015
DOI: 10.1111/ssqu.12221
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, Contact, and Religious Identity: A Cross‐National Analysis of Interreligious Favorability*

Abstract: Objectives This article examines cross‐national variation in interreligious favorability across the globe. We develop and test several hypotheses linking globalization to attitudes toward the religious other through mechanisms of religious belonging and contact. Methods Utilizing cross‐national data in 20 countries from the Pew Global Attitudes Surveys (2011), we run a series of multilevel and logistic regression estimations to test our hypotheses about global contact, religious identity, and interreligious fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
1
8
1
Order By: Relevance
“…Shifting from the category of “nonreligious” to “very religious” persons increases prejudice by 0.210 scale points—making this impact stronger than the direct contact effect. As such, these findings are fully consistent with previous studies (e.g., Pettigrew and Tropp, ; Ciftci, Nawaz, and Sydiq, ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Shifting from the category of “nonreligious” to “very religious” persons increases prejudice by 0.210 scale points—making this impact stronger than the direct contact effect. As such, these findings are fully consistent with previous studies (e.g., Pettigrew and Tropp, ; Ciftci, Nawaz, and Sydiq, ).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with these characteristics, numerous studies have concluded that strong religiosity is conducive to prejudice (e.g., Allport, ; Ciftci, Nawaz, and Sydiq, ; Hunsberger and Jackson, ). Although undeniably plausible, this does not necessarily imply that religious persons are hostile toward the “other” in any conceivable context.…”
Section: Intergroup Contact and Religiositymentioning
confidence: 85%
See 2 more Smart Citations
“…In fact, according to Pettigrew and Tropp (2006) any possible conflict between two religious' groups, if any, reduces significantly when the groups have any minor interaction within a social setting (Pettigrew and Tropp 2006). Ciftci, Nawaz, and Sydiq (2016) also find that contact between groups has a positive impact on tolerance levels, not only in a domestic context but also in a global one (Ciftci, Nawaz, and Sydiq 2016). Similar trends were found by Thomsen and Rafiqi (2017) when they measured intergroup contact among Danish populations and their affect on tolerance levels (Thomsen and Rafiqi 2017).…”
Section: Historical Background and Relevant Literaturementioning
confidence: 95%